FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL - JONI JONI; LINA LINA (Jurnal Bisnis dan Akuntansi, 2010)
The objective of this research is to test and analyze whether pro-fitability, firm size, assets growth, dividend, assets structure, and business risk influence to firm capital structure. Listed manufacturing companies at Indonesian Stock Exchange from period 2005 to 2007 were examined. Forty three companies met the criteria and were analyzed descriptive statistic and multiple regression were performed to test the hypotheses. The conclusion shows that assets growth, profitability, and assets structure influence firm capital structure of manufacturing companies. Firm size, dividend, and business risk do not influence firm capital structure.